EL ESPAÑOL EN EL AULA DE INGLÉS. UN ESTUDIO EMPÍRICO - Martín Martín, José Miguel (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This experiment explores the advantages of using the L1 in the EFL classroom in activities such as explicit presentation of form-based content. Two groups of 33 pupils -the control and the experimental- were taught a specific morphosyntactic structure -the passive- in five classes. Three tests were then administered -immediate, delayed and late- and the results compared. The independent variable was the use or non-use of the L1 in the five sessions of presentation and subsequent activities. The results of all parameters analyzed showed differences in favour of the control group; in many cases these differences were statistically significant according to Ttests applied at a significance level of 5% (a < .5). This suggests that, in a monolingual classroom, the minimal role played by the L1 accorded by the current orthodoxy of foreign-language teaching methodology should be revised; it does not, however, undermine the centrality of exposure to the L2 and interaction in it.